A Randomized Trial of Topical Anesthesia Comparing Lidocaine Versus Lidocaine Plus Xylometazoline for Unsedated Transnasal Upper Gastrointestinal Endoscopy. (2010) - Cheung, Justin; Goodman, Karen J; Bailey, Robert; Fedorak, Richard N; Morse, John; Millan, Mario; Guzowski, Tom; van Zanten, Sander Veldhuyzen
Abstract : BACKGROUND: The optimal topical anesthesia regimen for unsedated transnasal endoscopy is unknown. The addition of a nasal decongestant, such as xylometazoline (X), to a topical anesthestic may improve patient comfort. OBJECTIVE: To determine the effectiveness of lidocaine (L) versus L plus X (LX) for anesthesia in unsedated transnasal endoscopy. METHODS: Consecutive participants of the Aklavik Helicobacter pylori project were prospectively randomly assigned to receive LX or L for unsedated transnasal 4.9 mm ultrathin endoscopy. The primary outcome was overall procedure discomfort on a validated 10-point visual analogue scale (1 = no discomfort, 10 = severe discomfort). Secondary outcomes included pain, endoscope insertion difficulty, gagging, adverse events and encounter times. Results were presented as mean ± SD, difference in mean, 95% CI. RESULTS: A total of 181 patients were randomly assigned to receive LX (n=94) and L (n=87). Baseline characteristics between the two groups were similar (mean age 40 years, 59% women). Overall, patient procedural discomfort with LX and L were 4.2±2.4 versus 3.9±2.1, respectively (0.29; 95% CI −0.39 to 0.96). Transnasal insertion difficulty was significantly lower with LX than with L (2.4±2.1 versus 3.2±2.8, respectively [−0.80; 95% CI −1.54 to −0.06]). Compared with L, the use of LX was associated with significantly less time needed to apply anesthesia (2.4±1.8 min versus 3.5±2.2 min, respectively [−1.10; 95% CI −1.71 min to −0.50 min]) and less time for insertion (3.2±1.8 min versus 3.9±2.2 min, respectively [−0.70 min; 95% CI −1.30 min to −0.10 min]). Epistaxis was rare but occurred less frequently with LX (1.1%) than with L (4.6%) (P=0.19). CONCLUSIONS: LX did not improve patient comfort for transnasal endoscopy compared with L alone. However, LX was associated with less difficulty with endoscope transnasal insertion and reduced insertion time. Further studies on the optimal regimen and dosing of anesthesia are required.